Rosuvastatin protects against coronary microembolization-induced cardiac injury via inhibiting NLRP3 inflammasome-dependent pyroptosis. (25th November 2020) - Chen, A; Chen, Z.W; Qian, J.Y; Ge, J.B
Abstract: Background: Coronary microembolization (CME), a common reason for periprocedural myocardial infarction (PMI) after coronary interventions, bears very important prognostic implications. However, the molecular mechanisms related to CME remain largely elusive. Statins have been shown to prevent PMI, but the underlying mechanism has not been identified. Purpose: To determine whether NLRP3 inflammasome contributes to CME-induced cardiac injury and to investigate the effect of statin therapy on CME. Methods: In vivo study, CME models were established in C57BL/6J mice by injecting 500, 000 polyethylene microspheres (diameter 9 μm) into the left ventricle chamber with the occlusion of the ascending aorta. Mice with CME were treated with 40 mg/kg/d rosuvastatin orally or a selective NLRP3 inflammasome inhibitor MCC950 intraperitoneally (20 mg/kg/d). Cardiac function was evaluated by echocardiography. Cardiac histological analysis was performed. The NLRP3 inflammasome and pyroptosis-related genes and proteins were detected. Cardiac injury was evaluated by Heidenhain's iron hematoxylin stain and serum lactate dehydrogenase (LDH) measurement. Cardiac reactive oxygen species (ROS) production and mitochondrial morphology were also determined. In vitro study, H9c2 myoblasts, stimulated with the classic NLRP3 inflammasome activators lipopolysaccharide (LPS) plus nigericin (Nig), were used to reveal underlying mechanisms of the rosuvastatin's effects. Results: The expression of NLRP3, caspase-1 and interleukin-1β (IL-1β) were all increased and peaking at 3 days after CME. Mice treated with MCC950 and rosuvastatin showed improved cardiac contractile function and morphological changes, diminished fibrosis and microinfarct size, and reduced serum LDH level. Mechanistically, rosuvastatin decreased the expression of NLRP3, caspase-1, IL-1β and the pyroptosis executor Gasdermin D. Furthermore, reduced ROS level and alleviated mitochondrial damage were observed in rosuvastatin-treated mice. In vitro study, rosuvastatin effectively inhibited the activation of NLRP3 inflammasome induced by LPS and Nig in H9c2 cells, as evidenced by decreased expression of NLRP3, caspase-1, IL-1β and Gasdermin D. Flow cytometry revealed that rosuvastatin rescued LPS and Nig-induced caspase-1 activation from 22.2±1.6% to 4.09±0.85%. Meanwhile, the pyroptosis was also suppressed by rosuvastatin, indicated by the increased cell viability, decreased LDH and propidium iodide uptake. Similarly, rosuvastatin also reduced the level of ROS generation in vitro. Conclusions: NLRP3 inflammasome-dependent cardiac pyroptosis plays an important role in CME-induced cardiac injury and its inhibitor exerts cardioprotective effect following CME. We also uncover the anti-pyroptosis role of rosuvastatin in CME, which is associated with regulating mitochondrial ROS. Funding Acknowledgement: Type of funding source: None